Model alat uji permeabilitas lapangan untuk jenis tanah lempung. - Andius Dasaputra (UNIVERSITAS LAMPUNG, 2012)
The amount of water flowing through a certain area can be represented by the coefficient ofpermeability. Coefficient of permeability value is obtained by conducting laboratory test such asfalling head permeameter (FHP) or constant head permeameter (CHP). The equipment developedin this research can be used for field permeability test directly on the soil. The result of the testshows that the equipment can be used to determine coefficient of field permeability for clay type ofsoil. Results of permeability test based on FHP shows a little difference from the data based on theequipment model. Test on the field from 8 point location around Faculty of Engineering, LampungUniversity show that coefficient of permeability for clay about 10-6 until 10-7 cm/sec. This showsthat the equipment performs well for determining coefficient of permeability for clay soil.